Strategi Penyediaan Perumahan Masyarakat Berpenghasilan Rendah (MBR) Kota Cilegon - M Nalla Ramadhan; Asnita Frida Sebayang (Bandung Conference Series: Economics Studies, 2022)
Abstract. The increasing rate of population growth, the growing number of residents will result in increasing housing needs in Indonesia. This will affect all levels of society due to an increase in the number of housing needs (backlog), especially in low-income communities. The needs for housing needs to be balanced with the number of available houses so as to avoid gaps. The fulfillment of housing needs for the community will greatly assist in the implementation of education and improving the quality of life so as to create a better life structure. This research is a descriptive-quantitative research that aims to determine the strengths, weakness, opportunities and threats in the strategy of providing housing for low-income people. The analytical method used in this research is SWOT analysis. The data used in this study are primary data obtained through questionnaires and interviews with the government or related agencies, implementing banks and developers in housing construction for low-income people. Based on the results of research and discussion, the strategy obtained from the SWOT analysis in this study is the turn around strategy which is known through the analysis of weaknesses and opportunities (Weakness-Opportunity). Improving the quality of licensing services both in online and offline systems with coordination and integration of related agencies. The government is increasing supervision on the selection of home ownership financing and the process of subsidized housing development. Abstrak. Meningkatnya laju pertumbuhan penduduk, berkembang pula jumlah penduduk maka akan mengakibatkan kebutuhan rumah yang semakin meningkat di Indonesia. Hal ini akan berpengaruh pada seluruh lapisan masyarakat karena adanya peningkatan angka kebutuhan rumah (backlog) terutama pada masyarakat berpenghasilan rendah. Kebutuhan akan perumahan perlu di imbangi dengan jumlah rumah yang tersedia sehingga terhindar dari terjadinya kesenjangan. Terpenuhinya kebutuhan rumah bagi masyarakat akan sangat membantu dalam terlaksananya pendidikan dan peningkatan kualitas hidup sehingga menciptakan susunan hidup yang lebih baik. Penelitian ini merupakan penelitian deskriptif-kuantitatif yang bertujuan untuk mengetahui kekuatan, kelemahan, peluang, dan ancaman dalam strategi penyediaan perumaan bagi masyarakat berpenghasilan renah (MBR). Metode analisis yang digunakan dalam penelitian ini adalah analisis SWOT. Data yang digunakan dalam penelitian ini data primer yang didapat melalui kuisioner dan wawacara terhadap pemerintah atau dinas terkait, bank pelaksana dan pengembang dalam pembangunan perumahan bagi masyarakat berpenghasilan rendah. Berdasarkan hasil penelitian dan pembahasan, Strategi yang didapat dari analisis SWOT dalam penelitian ini yaitu strategi turn around yang diketahui melalui analisis kelemahan dan peluang (Weakness-Opportunity). Meningkatkan kualitas pelayanan perizinan baik dalam sistem daring maupun luring dengan kordinasi dan integrasi dinas terkait. Pemerintah meningkatkan pengawasan pada seleksi pembiayaan kepemilikan rumah dan proses pembangunan perumahan subsidi.